Desenvolvimento de um robô de mini sumô autônomo destinado a competições de robótica - Gallina, Arthur (2019)
Technological growth is continuous and the automation of tasks and processes are increasingly. In this sense, robotics aims to develop the automation of tasks performed by people, bringing benefits to society through more accurate work, faster and lower costs. However, one of the main challenges of robotics is to obtain the greatest possible autonomy by integrating the robot with other aspects such as perception capacity, action capacity, robustness and decision making. Thus, a scenario in which these autonomous robots are seen are the robotics competitions, which have several categories, such as mini sumo. Thus, aiming to obtain an optimal control logic, this work is inserted in autonomous robotics and aims to apply the Supervisory Control Theory (SCT), proposed by Ramadge and Wonham, in 1989, for Discrete Event Systems (DES) aiming to obtain a control logic from an autonomous mini sumo robot. Moreover, the present work also aims to stimulate research and promote the dissemination of UTFPR courses in these competitions. At the end of the development the modeled and implemented logic worked correctly, making the robot able to participate in competitions.